Theorising Diaspora: Nationalist Discourse in Shaping Diasporic Subjects - Abouyassine, Brahim (International Journal of Language and Literary Studies, 2023)
Identities of individuals or communities undergo waves of changes and modifications of the constituents of the embodiment they are represented in. Diasporic subjects play a crucial role in the process of identifying the individuals as well as the communities since they reintroduce new perspectives to approach allegiances and categorisations. The paper debates the diaspora from a theoretical perspective focalising on the role of the positionality of the bearers in participating in the construction of the diasporic apprehension in light of the nationalist discourse. It probes the dispersion and detachment of the diasporic subject and the probations of developing diverse identity allegiances while associating themselves to a group or community. It presents different strategies of the individuals in reconnecting to an embodiment of articulations. The very particular elements by which one can distinguish a diasporic subject from those of the others are, themselves, open to restructuring and reformulating. Diasporic identities are not the only variable that goes through the process of development and re-articulation that introduces new aspects to the entity of diaspora. As much as the reformulations that are made to the subjects themselves, what makes up their beings is affected by changes in perspectives toward them. Therefore, the process of re-enunciation contributes to adding new dimensions to the fundamental characteristics that make them distinctive rather than simply reproducing different viewpoints on the subjects and changes to what establishes them.